أثر التدخل الخارجي على التنمية المستدامة في ليبيا (Comprehensive Journal of Science, 2025)
External intervention is one of the causes that leaves a clear, long-term impact on the security, political, and economic situation of countries. These external powers, whether international or regional, play a fundamental role in changing the state of nations. External intervention has several causes and factors—some material, some political or economic, and it may also be military or religious. It is also considered an intervention to stir stagnant waters within states. The country experiencing conflict may resort to allying with a third party to overcome internal conflicts or civil wars related to the regime and its legislation, which may persist for many years, negatively affecting the goals of sustainable development and the improvement of living conditions for individuals in the future. One of the most important issues Libya seeks to develop after the events of 2011 is sustainable development, despite all the obstacles and challenges it faces, and its efforts to achieve even a portion of the Sustainable Development Goals defined by the United Nations as seventeen goals set for all countries. Libya needs a bold step to revive its economy, which has suffered from security instability and political problems whose critical effects still dominate the economic situation.The aim of the research is to clarify the weaknesses in sustainable development as a result of the external interventions that Libya has suffered over the years. Through the research divisions, we sought to answer the research question: The impact of external intervention on sustainable development in Libya, and the researcher sought to clarify the most important challenges and obstacles facing progress and the improvement of income levels, education, and health.In the first section: the theoretical framework, it is divided into the concept of external intervention, the influencing factors, and the concept and importance of sustainable development. The second section, the analytical framework, shed light on what has been achieved and what has not from the development goals that came to a halt after the events of 2011, and the development goals that governments are trying to achieve after those events. It also explores the reasons behind the weaknesses in these goals due to external interventions in Libya. The research concludes with a summary, a number of findings, and recommendations. .